2020
DOI: 10.15407/dse2020.01.079
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Effect оf Education оn Earnings іn Urban аnd Rural South Africa: а Further Update

Abstract: T. ZWANE is used to address possible endogeneity bias due to reverse causation between earnings and education. Aft er controlling for endogeneity, we found that an additional year of education increased an individual's earnings by 37.8 % in the full sample. Interestingly, the coeffi cient of education was found to be positive and statistically signifi cant in both samples (urban and rural), reinforcing the results of the full sample. However, despite the coeffi cient of years of education being similar in dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Growth, employment and redistribution advocated for a decrease in public expenditure, which resulted in the government failing to address the education imbalances, including that of teacher compensation. Zwane (2020) compared earnings between South Africa's urban and rural teachers relying on the National Income Dynamics data for the years 2008-2017. The study by Zwane (2020) revealed that an increase in a person's education qualification levels resulted in a corresponding increase in earnings equal to 37.8%.…”
Section: Career Adaptability Work Resources and Employee Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth, employment and redistribution advocated for a decrease in public expenditure, which resulted in the government failing to address the education imbalances, including that of teacher compensation. Zwane (2020) compared earnings between South Africa's urban and rural teachers relying on the National Income Dynamics data for the years 2008-2017. The study by Zwane (2020) revealed that an increase in a person's education qualification levels resulted in a corresponding increase in earnings equal to 37.8%.…”
Section: Career Adaptability Work Resources and Employee Healthmentioning
confidence: 99%
“…Zwane (2020) compared earnings between South Africa's urban and rural teachers relying on the National Income Dynamics data for the years 2008-2017. The study by Zwane (2020) revealed that an increase in a person's education qualification levels resulted in a corresponding increase in earnings equal to 37.8%. Sadly, the study further reveals that the education impact on teachers' earnings is higher in absolute values for teachers in urban areas as they bagged 44.4% in total returns to education, compared to 33% for teachers in rural areas.…”
Section: Career Adaptability Work Resources and Employee Healthmentioning
confidence: 99%
“…As a rule, economic theory also recognises that investments in education and the development of competences contribute to better income in the lives of people (Becker, 1962). A significant number of empirical studies confirm that the level of education has an impact on the level of earnings of individuals (for example : Card, 1999;Efendic & Pugh, 2018;Harmon, Oosterbeek & Walker, 2003 Pereira & Martins, 2014;Psacharopoulos, 1994;Psacharopoulos & Patrinos, 2004;Risal & Gupta, 2017;Yakum & Kifem, 2018;Zwane, 2020). There is also compelling evidence that the better-educated individuals have higher earnings and less probability of being unemployed (for example Mulligan, 1997;Patel, 2019).…”
mentioning
confidence: 99%
“…Determinants of savings in urban and rural households: case of South Africa pulated, and had limited economic opportunities (May & Norton, 1997;De Vos et al, 2020). In a recent study, Zwane (2020) claims that the apartheid system forced the black population into homelands or rural areas where they were not permitted to obtain quality education which might lead them to aspire to positions in society that they would not be allowed to hold. Th e colonial and legislated oppressive regime of apartheid precluded opportunities and development in formerly black African areas (Von Fintel & Fourie, 2019).…”
mentioning
confidence: 99%
“…In their work, Ashley and Maxwell (2001) argued that South Africa is one of the countries where poverty, unemployment, and inequality are prominent and seem to be worsening for the black African sections of society, particularly those living in rural areas. In their landmark statement, Ashley and Maxwell (2001: 395), cited in Zwane (2020), argued that: "[p]overty is not only widespread in rural areas [where Africans live], but most poverty is rural, at least for now".…”
mentioning
confidence: 99%